CURRENT PROBLEMS OF MICROBIOLOGY (World Bulletin of Public Health, 2023)
This article explores the contemporary challenges faced by microbiology, encompassing issues such as antibiotic resistance, the emergence of new pathogens, the intricate dynamics of the microbiome, and the evolving landscape of environmental microbiology. A comprehensive literature analysis is conducted to shed light on the current state of microbiological research. The methods, results, and discussions sections provide insights into ongoing studies and highlight potential avenues for future research. The conclusions and suggestions section offers recommendations to address these challenges and pave the way for advancements in the field.
Keywords: Microbiology; antibiotic resistance; emerging pathogens; microbiome